An extensive investigation of structural, electronic, thermoelectric and optical properties of bi-based half-Huesler alloys by first principles calculations - Dey, Aditya; Sharma, Ramesh; Dar, Sajad Ahmad (Materials today communications, 2020)
•The structural, electronic, optical and thermoelectric properties of ZrRhBi, ZrIrBi and HfRhBi alloys are studied.•Different exchange potentials have been employed to accurately predict the properties.•They behave as narrow to moderate gap semiconductor.•They have excellent thermoelectric materials having high power factor and figure of merit.•Their optical response in various ranges of electromagnetic spectrum opens prospect of using them in certain optical devices. Half Huesler (HH) alloys have been a hot topic of research due to their fascinating properties and applications in several fields. There are several HH alloys been studied and this work is based on three Bismuth based HH alloys, ZrRhBi, ZrIrBi and HfRhBi, of which we have presented an extensive study on the structural, electronic, thermoelectric (TE) and optical properties using ab-initio density functional theory (DFT) calculations. The previous work on these alloys reported their stability and electronic properties stating that they possess good TE response which was done using DFT with PBE-GGA functional (J. Mater. Chem. A,5(13), 2017). In our study, we have used different exchange functionals to investigate these properties and observed that using nmBJ (new modified Becke–Johnson) potential, we can obtain enhanced band gap and TE response (high figure of merit, ZT and power factor, PF) of these alloys as compared to previous report and fascinating optical properties as well. Our results show that ZrIrBi and HfRhBi are narrow-gap and ZrRhBi is a moderate gap semiconductor. All of these alloys have excellent ZT values of around 0.7 at room temperature. The optical properties show that these compounds have low absorbance, moderate reflectivity and low optical conductivity in visible region. The contrasting behaviour of their optical properties with respect to the regions of electromagnetic spectrum and their electronic properties suggests that they can be effectively used in optoelectronics and various optical devices. Also, their high ZT values both in low and high temperatures open up a possibility to use them for various TE applications.